"Knowing Well, Being Well: Well-Being Born of Understanding." Introducing a New Open-Access Section for the American Journal of Health Promotion. Issue 6 (July 2020) - Terry, Paul E.
A time-honored principle in education is that changes in knowledge, attitudes, and beliefs are precursors to changes in actions or behaviors. Nevertheless, health promotion professionals occasionally hear the bromide that "people know what they're supposed to do, they just don't do it!" What does it mean to know something really well? And when is knowledge influential enough that it affects our very way of being? This editorial introduces a new section for the American Journal of Health Promotion called "Knowing Well, Being Well: Well-being born of understanding" (KWBW). Premiering in this issue of the journal, KWBW will be led by coeditors Drs Sara Johnson and David Katz, two of the most recognized and respected leaders in health promotion. Although today's health promotion practitioners seem intent on moving "from wellness to well-being, " our discipline is in the nascent stages of reconciling theories of behavior change and pathways to well-being. "Knowing Well, Being Well" will chart a course to explore how knowledge, supportive environments, and purposeful living contribute to health, happiness, and life satisfaction.